2007
DOI: 10.1007/s00192-006-0269-5
|View full text |Cite
|
Sign up to set email alerts
|

A radiological study on the anatomical proximity of the ureters and the cervix

Abstract: In order to evaluate risk factors for anatomical proximity between the cervix and the ureters the distance between the ureters and the cervix was measured in 499 computerized tomography (CT) studies at the most dorsal reflection of the ureters. The relationship between the ureter-cervical distance and the presence of pelvic pathology was assessed by correlation tests and regression analysis. Of the 499 CT studies, 252 demonstrated radiographic pathologies. Among abnormal scans, 126 (50%) involved cervical path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Any combination of these injuries may occur. The close proximityof the ureter to the uterus and cervix with limited exposure increase the chances of injury especially if the uterus is enlarged , the dissection is difficult due to malignancy and adhesions due to pelvic inflammatory disease radiation therapy, anatomical anomalies of the urinary tract also increases chances of injury [11,12]. Our series similarly demonstrated that abdominal hysterectomy was the most common cause for iatrogenic ureteric injuries.…”
Section: Discussionsupporting
confidence: 59%
“…Any combination of these injuries may occur. The close proximityof the ureter to the uterus and cervix with limited exposure increase the chances of injury especially if the uterus is enlarged , the dissection is difficult due to malignancy and adhesions due to pelvic inflammatory disease radiation therapy, anatomical anomalies of the urinary tract also increases chances of injury [11,12]. Our series similarly demonstrated that abdominal hysterectomy was the most common cause for iatrogenic ureteric injuries.…”
Section: Discussionsupporting
confidence: 59%
“…When ureteral trauma is suspected, CT urography (CTU) is considered the gold standard tool for diagnosis according to the European Association of Urology (EAU) [ 19 ] and the American Urological Association (AUA) guidelines [ 20 ]. In fact, CTU allows the demonstration of ureteral contrast extravasation, urinoma, ascites, and fistulae, and can be used to study the entity of the lesion to guide the treatment planning [ 21 , 22 ]. Retrograde or anterograde pyelography are also sensitive radiographic tests for ureteral injury, while also allowing the simultaneous stenting procedure [ 10 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in patients with early leakage resolution, no stent replacement was needed and no procedural complications were reported. However, the persistent leakage of a fistulous output makes conservative treatment less valid [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of sectional anatomy has increased with the introduction of various imaging techniques such as CT and magnetic resonance imaging (MRI) because modern medicine uses these imaging techniques for preoperative diagnosis, radiotherapeutic planning, and preoperative simulation. The radiological appearance of anatomical structures in healthy women has been described in the literature (Bazot et al, ; Hurd et al, ; Gemer et al, ; Mauroy et al, ; O'Connell et al, ; Chen et al, ). However, the radiological imaging of surgical anatomical structures has not been investigated.…”
Section: Discussionmentioning
confidence: 99%